Arabic Language Learning Program in the Language Tourism Village in Terms of Learning Management/برنامج تعليم اللغة العربية بقرية السياحة اللغوية في ضوء الإدارة التعليمية - Wulandari, Nuning Putri (UIN Raden Mas Said Surakarta, 2020)
The Language Tourism Village Program in Pakel is a program that teaches Arabic which requires management in the teaching process. The purpose of this study was to determine and describe the implementation of the Arabic language program in the Arabic tourism village in Pakel village, Karangpandan, Karanganyar. The results of this study indicate: 1) in planning, the purpose of learning Arabic in the Language Tourism Village in Pakel uses the curriculum applied in the Language Tourism Village at the Ali Royah Sukabumi Islamic Boarding School which has been designed completely by the curriculum developed by the Arabic book author Baina yadaik; 2) All teachers in this program are graduates of the Ali Rayah Sukabumi Islamic boarding school; 3) Implementation, consisting of 3 activities, namely: initial activities, core activities, and final activities. 4) Evaluation, held every two weeks.